2015
DOI: 10.1016/j.jphs.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of rocuronium with human liver cytochromes P450

Abstract: Rocuronium is a neuromuscular blocking agent acting as a competitive antagonist of acetylcholine. Results of an inhibition of eight individual liver microsomal cytochromes P450 (CYP) are presented. As the patients are routinely premedicated with diazepam, possible interaction of diazepam with rocuronium has been also studied. Results indicated that rocuronium interacts with human liver microsomal CYPs by binding to the substrate site. Next, concentration dependent inhibition of liver microsomal CYP3A4 down to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Firstly, patients taking different statins have varying effects on CYP3A4 isoenzyme. Atorvastatin has the strongest effect, simvastatin has a moderate, while fluvastatin has a weak effect [38,40]. Secondly, this study was not randomized and the sample size was small.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Firstly, patients taking different statins have varying effects on CYP3A4 isoenzyme. Atorvastatin has the strongest effect, simvastatin has a moderate, while fluvastatin has a weak effect [38,40]. Secondly, this study was not randomized and the sample size was small.…”
Section: Discussionmentioning
confidence: 95%
“…A moderate inhibition was observed for CYP2C19. Meanwhile, rocuronium displayed no or weak inhibition of CYP1A2, 2A6, 2B6, 2C9, 2D6 and 2E1 activities . Anzenbacherova et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…added that the elevated infusion requirements in patients on CAT were independent of serum levels of phenytoin and while not significant, also reported that recovery from neuromuscular block was faster in the CAT group as compared to controls [ 40 ]. Additional studies have found that utilization of ROC in patients on CAT may be due in part to long term effects of CAT on liver hypertrophy and higher levels of cytochrome P450 (CYP) [ 41 ], and CYP3A4 was found to interact with ROC [ 42 ], suggesting that the elevated need for ROC in patients on CAT may be associated with elevated liver enzymes that sequester ROC. While it has been shown that CAT can affect NMBA dosing requirements, the variability among patients is not well understood, and it remains unclear why patients with CP who are not on CAT might require more ROC for intubation than controls [ 32 , 39 ].…”
Section: Introductionmentioning
confidence: 99%